Long-term survival with multidisciplinary treatment in metastatic sarcomatoid renal cell carcinoma: a case report and literature review - Li, Xin; Wang, Weijia; Meng, Lingjun; Liang, Honglu (Frontiers in Oncology, 2025)
BackgroundSarcomatoid transformation in renal cell carcinoma, termed sarcomatoid renal cell carcinoma (SRCC), is associated with aggressive behavior and an unfavorable prognosis. The presence of sarcomatoid differentiation poses a therapeutic challenge due to limited response to existing systemic therapies; however, advances in drugs with immune checkpoint inhibitor (ICI) have improved response rates.Case descriptionWe report the case of a middle-aged woman diagnosed with multiple metastatic SRCC, treated with a combination of pembrolizumab plus axitinib as first-line therapy, transarterial chemoembolization, and nephrectomy. The patient ultimately achieved complete remission but presented with severe colitis symptoms. Following the cessation of pembrolizumab and axitinib therapy for 1 year, her colitis symptoms gradually resolved, with no evidence of recurrence or metastasis observed during that time. Her survival period has now extended beyond 2.5 years.ConclusionMetastatic sarcomatoid renal cell carcinoma is associated with very poor prognosis, with a survival period of <1 year despite systemic therapy. In this present case, the patient achieved long-term survival following multidisciplinary treatment—a rare occurrence worthy of report.